Land and identity in South Africa: An immanent moral critique of dominant discourses in the debate on expropriation without compensation - Vorster, Nicolaas (HTS teologiese studies, 2019)
Ownership is an important identity marker. It provides people with a sense of autonomy, rootedness and opportunity. This essay examines the oral submissions of civil organisations to the Joint Constitutional Review Committee (04–07 September 2018) about the issue of land expropriation without compensation. The discussion pays specific attention to the philosophical understandings of land and identity that emerged during the hearings. Three dominant trajectories came into play, namely land as commodity, land as social space and land as spiritual inheritance. Some submissions espoused more than one view, which indicates that the boundaries between the identified paradigms are permeable. However, even those presentations tended to prioritise one approach above the others. Besides identifying the main approaches to land and identity, this essay also provides an immanent critique of their moral assumptions. In contrast to a transcendental approach, an immanent critique asks questions from ‘within’ and evaluates paradigms in terms of their plausibility, universal applicability, ethical consistency and moral integrity.